Object oriented programming: what is IT talking about? - Blansit BD (Journal of Electronic Resources in Medical Libraries)
A familiarity with programming methods aids the librarian in seroing as part of a team with computer profeSSionals. In school, many librarians were required to write simple computerprograms using methods from Procedural Programming, although this term may not have been explicitly used. In reading more modern technical literature, the librarian often comes across the term 'Object Oriented Programming' (OOP), which has been increasingly used in the past few decades. To gain familiarity with the use and di.fJerences of these two methods, this article presents a simple mathematical problem and how it would be approached in both Procedural and Object Oriented Programming. It then moves to more complex situations that highlight the advantages of using OOP. This article also highlights similarities and di.fJerences between these two Widely usedprogramming methods as well as steps in the design process that make use of the traditional librarian skills ofclassification.